Risk factors for urinary incontinence among women aged 60 or over with hypertension in Taiwan - Keng-Ming Chang; Ching-Hung Hsieh; Han-Sun Chiang; Tian-Shyug Lee (Elsevier, 2014)
Objective: To assess the associated risk factors and the prevalence of urinary incontinence (UI) among women with hypertension (H/T) aged 60 or over in Taiwan. Materials and Methods: A total of 2410 women aged 60 or over were selected by a multistage random sampling method and a total of 1519 women completed the face-to-face interviews. Only women who answered "yes" to the question "Do you have H/T?" were included in the H/T sample. The factors were assessed by frequency and Pearson's χ2 test using a significance level of p < 0.05. Logistic regression was used to investigate the significance of dichotomous dependent variables. Results: A total of 39.7% (602 women) interviewees had H/T, among which 39.9% (240 women) had UI symptoms. The prevalence of UI among women aged 60 or over with or without H/T was significantly different (p = 0.006). Risk factors were age [odds ratio (OR) = 1.043, 95% confidence interval (CI) 1.016-1.071, per year], diabetes mellitus (DM) (OR = 1.653, 95% CI 1.105-2.474), previous urinary diseases (OR = 3.462, 95% CI 2.260-5.301), and body mass index (BMI; OR = 1.060, 95% CI 1.012-1.110, per unit). There was no significant association between UI and drug allergy, smoking, hysterectomy, hormone therapy, or gynecological surgery. Conclusion: UI can be a frequent and annoying problem for aged women. In women with H/T, UI is significantly related to risk factors such as age, DM, BMI, and urinary diseases. In addition, BMI is considered a key risk factor for H/T. Therefore, effective control of BMI would help in controlling H/T and UI in aged women.